The Socio-Cultural Meaning of Traditional Games on the Motivation and Motor Skills of Elementary School Students - Kamilah Insani; Anida Nuraisyah Budiman; Aam Ali Rahman (Jurnal Pendidikan Jasmani (JPJ), 2026)
The decline in traditional game practices due to the dominance of technology has hindered the cultivation of socio-cultural values and reduced opportunities for developing learning motivation and motor skills among elementary school students. This study aims to explore the socio-cultural meanings of traditional games and their roles in enhancing students’ motivation and motor skills using a qualitative method with an intrinsic case study approach. Participants were selected through purposive sampling, consisting of the principal, Physical Education teachers, and 28 fourth-grade students relevant to the issue of low traditional game practice. Data were analyzed using thematic analysis to identify patterns of meaning, experiences, and student interactions during play activities. The results show that traditional games can enhance enthusiasm, motivation, motor skills, cooperation, honesty, social interaction, and students’ character, supported by the role of teachers and schools in providing facilities, supervision, and learning policies. This study emphasizes the importance of traditional games as a local-wisdom-based PE learning strategy to holistically develop students’ motor, social, and affective aspects.